Identification of Factors Causing Cost Increases in Infrastructure Projects - Harind Aditya Putra (Eduvest - Journal of Universal Studies, 2025)
Cost is one of the important parameters of the success of a construction project. Rising costs are the biggest challenge faced by the construction industry around the world. There are six groups that cause the increase in construction, namely, Technical, Financial, Management, Political, Resources, and Environment. The research aims to identify the factors that cause the increase in costs and how these factors affect the increase in costs. The research was conducted on one leading construction company, where 5 infrastructure projects were selected as the object of the research. The research is a qualitative research that uses two types of data, secondary data from documentation studies and primary data from questionnaires. Secondary data was obtained from the study in the document and poured into  a fishbone diagram. The results of the initial identification were then outlined in a questionnaire to measure the Relative Importance Indices (RII). RII is a method to determine the relative importance of various factors causing cost increases. From the results of data analysis, 10 main factors were obtained which were grouped into 3 groups; Very Important, Important and Quite Important. In addition, an additional analysis was carried out by measuring RII based on 4 types of projects, namely road construction, water buildings, pipeline installations, and runways. The land acquisition factor is a very important factor in 2 types of projects, namely roads and water buildings. This is because both types of projects involve a long or large implementation area.